Improved Glucose‐Neopentyl Glycol (GNG) Amphiphiles for Membrane Protein Solubilization and Stabilization. Issue 2 (28th November 2013) - Cho, Kyung Ho; Bae, Hyoung Eun; Das, Manabendra; Gellman, Samuel H.; Chae, Pil Seok
Abstract Membrane proteins are inherently amphipathic and undergo dynamic conformational changes for proper function within native membranes. Maintaining the functional structures of these biomacromolecules in aqueous media is necessary for structural studies but difficult to achieve with currently available tools, thus necessitating the development of novel agents with favorable properties. This study introduces several new glucose‐neopentyl glycol (GNG) amphiphiles and reveals some agents that display favorable behaviors for the solubilization and stabilization of a large, multi‐subunit membrane protein assembly. Furthermore, a detergent structure–property relationship that could serve as a useful guideline for the design of novel amphiphiles is discussed.